Prophylactic effects of Ixora coccinea leaf on the haematological, biochemical, and atherogenic profile in male Wistar rats administered anticancer drug Cisplatin - Solomon Agu; Veronica Iyamu Ochigbo; Victory Oyare Akoh; Awulu Audu Audu; Nathaniel Daniel Rabo; Christian Okechukwu Ezihe (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: This study was aimed at investigating the prophylactic effects of hydroethanolic extract of Ixora coccinea leaf (HEICL) on Cisplatin (cis diamminedichloroplatinum-II, CDDP)-induced alteration in atherogenic, haematological, and biochemical profiles in male Wistar rats Experimental: Thirty male rats were assigned into 6 groups (n=5) in which groups A, B, C, and D received normal saline (0.2 mL), CDDP (10 mg/kg), HEICL at 200 mg/kg, and HEICL at 400mg/kg. Groups E and F received CDDP 10 mg/kg with HEICL at 200 mg/kg, and 400 mg/kg, respectively. Results: The phytochemical analysis of the AEAC revealed the presence of some phytochemical constituents such as alkaloids, flavonoids, saponins, tannins, reducing sugar, phenol, resin, and volatile oil. However, glycosides, steroids, and anthraquinone were absent. The Acute toxicity result indicated that HEICL has an LD50 above 5000mg/kg. CDDP caused a significant (P<0.05) decrease in the haematological parameters relative to the control but administration of CDDP with HEICL improved the parameters. CDDP caused a significant (P<0.05) increase in the levels of triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL), but a significantly (P<0.05) lower level of HDL. Treatment with CDDP and HEICL significantly (P<0.05) abrogated these CDDP-induced alterations. Similar ameliorative effects of HEICL were found in CDDP-induced alterations in atherogenic indices, such as Castelli's Risk Index I (CRI-1), Castelli's Risk Index II (CRI-II), Atherogenic Coefficient (AC), and Atherogenic Index of Plasma (AIP) indices relative to the control. Recommended applications/industries: The above study suggests that HEICLmay be useful in treating heart conditions because it protects against CDDP-induced alterations in the haematological, lipid, and atherogenic parameters.